Kajian tentang Penerapan Community Based Tourism di Daya Tarik Wisata Jatiluwih, Tabanan, Bali - Dyah Krismawintari, Ni Putu; Rai Utama, I Gusti Bagus (Jurnal Kajian Bali (Journal of Bali Studies), 2019)
Jatiluwih Village is a tourist village located in Penebel District, Tabanan Regency. This tourist village has a beautiful natural panorama with unique terraces at the nearby Mount Batukaru. This study uses a qualitative research approach with a type of descriptive research. The formulation of the problem studied by researchers was twofold, namely: (1) the application of the CBT concept carried out by the Jatiluwih Tourism Village authority in managing sustainable tourism attractions (2) the role played by relevant stakeholders. This study concluded that the management of Jatiluwih DTW has applied the principles of a healthy economy, development for the welfare of local communities; conserve nature so that the environment can be well maintained, healthy culture by contributing to the cultures that exist in rural communities, and applying the principle of tourist satisfaction. This study suggests that the "subak" system and natural landscape are maintained because they are an indicator of the satisfaction of tourists visiting Jatiluwih. Keyword: Community based tourism, Jatiluwih, World cultural heritage, Subak, Water irigation.